Death rate of the population of Tomsk Region for last two decades and measures on its decrease - V. F. Oleinichenko; G. I. Mendrina; S. M. Khlynin; D. Ye. Kalinkin; N. Ya. Nesvetailo; R. M. Takhauov; A. B. Karpov; M. A. Varlakov (Бюллетень сибирской медицины)
Mid-annual indicators of the general death rate during the period with 1996 on 2000 of on Tomsk Region, as well as on to the Siberian Federal district, and as a whole across the Russian Federation practically did not differ from similar indicators during the period with 1992 on 1996 of (their distinctions are doubtful — p > 0,05). Despite some decrease in rates of growth of death rate in 2001—2005 of, its level remains high — in 2001 it was 13,3, and in 2005 — 14,5 on 1000 population. The greatest number of people dies of illnesses of system of blood circulation, accidents, poisonings and traumas, new growths. Relative density died of the specified reasons from number of all died made in 2005 according to — 46,3%, 15,7% and 14,0%. Especially attracts attention growth of death rate of the population of area in 2,6 times in 2005 in comparison with 2001 from the reasons connected with the use of alcohol growth of death rate from the given reasons at persons of able-bodied age is More expressed. Mid-annual level of parent death rate in 2001—2005 of has decreased in comparison with 1996—2000 of on 29,2%. Strengthening of health is spent to areas not only women and children, but also all population the big complex of the actions directed on decrease of parent and infantile death rate, preventive maintenance of illnesses of system of blood circulation, etc.